Formation Mechanism and Size Prediction Models for Double Emulsion CO2 Solvents. Issue 19 (18th August 2020) - Kim, Seonggon; Xu, Ronghuan; Lim, Hwan Suk; Kang, Yong Tae
Abstract: Double‐layered emulsion is a structure that has one more layer over the droplet, which is developed to protect the core material and is applicable to various fields such as food, cosmetic and CO2 capture. However, the mechanism of double emulsion formation is not well established. In this study, the manufacturing process of hybrid double layered emulsion CO2 solvents is analyzed to clarify the mechanism of droplet formation and to control encapsulation of chemical absorbent. The droplet formation models are developed by considering dimensionless numbers, which can predict the size of inner and middle droplets of the double emulsion structure. The droplet formation models are verified experimentally. The number of encapsulated solvents can be precisely controlled according to optimum frequencies at which the inner and middle droplets are effectively formed. In particular, the middle phase, which is the ultraviolet curable material, protects inner cores and the thickness of middle phase (shell thickness) can be predicted. Optimum ratio of middle droplet diameter to inner droplet diameter is in the range of 0.7–0.93. The optimal conditions of droplet formation are proposed by the developed models, and it can be extended to other microfluidic devices. Abstract : A manufacture of double‐layered emulsion CO2 solvents is analyzed using volume of fluid model, which can control the formation modes and droplet diameters based on dimensionless correlations. In the experiment, the droplet size can be predicted with maximum error of 4.7%, and when the ratio of inner to middle diameter is larger >0.94, the rupture of double emulsion is occurred.